Kontribusi Kesabaran terhadap Flourishing pada Ibu Banyak Anak - Adhitiawan, Rasha Paramitha; Handayani, Eko (Syntax Corporation, 2025)
Multiple-children mothers face complex challenges that can hinder their well-being. Flourishing is regarded as the main standard of well-being, measured through five PERMA elements: positive emotions, engagement, positive relationships, meaning, and accomplishment. Patience is regarded as a personality characteristic that contributes to well-being. This study aims to examine the contribution of patience to flourishing among multiple-children mothers. Flourishing is measured using The PERMA-Profiler, while patience is measured based on the 3-Factor Patience Scale consisting of Daily Hassles Patience, Life Hardship Patience, and Interpersonal Patience. The research was conducted quantitatively with 131 participants and analyzed using linear regression analysis. Results show that patience, both as a whole and in each of its factors, contributes positively and significantly to all elements of flourishing. The largest contribution was found in Daily Hassles Patience toward positive emotions (12.2%). These findings highlight the important role of patience in supporting the achievement of flourishing among multiple-children mothers.